2016
DOI: 10.1103/physrevd.93.094514
|View full text |Cite
|
Sign up to set email alerts
|

Fast estimator of Jacobians in the Monte Carlo integration on Lefschetz thimbles

Abstract: A solution to the sign problem is the so-called "Lefschetz thimble approach" where the domain of integration for field variables in the path integral is deformed from the real axis to a sub-manifold in the complex space. For properly chosen sub-manifolds ("thimbles") the sign problem disappears or is drastically alleviated. The parametrization of the thimble by real coordinates require the calculation of a jacobian with a computational cost of order O(V 3 ), where V is proportional to the spacetime volume. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 14 publications
3
57
0
Order By: Relevance
“…Certainly one may improve the determination of W by considering a full correlation matrix of 4-point correlators, but we found that the simple correlator (22) entirely dominates the signal. We implemented the determination of W based on (22) for both the 2-d and the 4-d cases for the same values of N s as studied for the condensation thresholds.…”
Section: Particle Condensation and Scattering Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly one may improve the determination of W by considering a full correlation matrix of 4-point correlators, but we found that the simple correlator (22) entirely dominates the signal. We implemented the determination of W based on (22) for both the 2-d and the 4-d cases for the same values of N s as studied for the condensation thresholds.…”
Section: Particle Condensation and Scattering Datamentioning
confidence: 99%
“…The first successful dual representation was discussed by Endres in [6,7] and since then the complex φ 4 field has been used as a model system for many important developments of worldline techniques [8][9][10][11][12][13][14][15][16][17][18], as well as as a reference system for other approaches to overcome the complex action problem (see, e.g., [19][20][21][22][23][24] in this context).…”
Section: Introductionmentioning
confidence: 99%
“…In the GLTM [2], we deform the integration contour from R n to an n-dimensional real manifold in C n by using the so-called holomorphic gradient flow, which makes the sign problem milder. The holomorphic gradient flow is defined by the differential equation…”
Section: Generalized Lefschetz-thimble Methods (Gltm)mentioning
confidence: 99%
“…(See, however, ref. [26].) It should also be noted that one can include fermions in the CLM with the cost of O(V ) for the system size V , whereas in the GLTM, it requires O(V 3 ).…”
Section: Jhep06(2017)023mentioning
confidence: 99%